Patients´ beliefs and headache-related disability - Vieira, Rebeca Veras de Andrade; Mercante, Juliane Prieto Peres; Perboni, Talita Souza; Will, Walkyria Busato; Zibetti, Murilo Ricardo; Gomes, William Barbosa; Gauer, Gustavo (Headache Medicine, 2024)
Abstract There is a lack of studies investigating the associations between modifiable psychological factors in migraine more comprehensively. The present study aimed to investigate the associations between self-efficacy and locus of control beliefs, cognitive distortions, depression, anxiety, psychopathological symptoms, headache headache-related disability, headache frequency, and severity in migraine patients. In addition, we compared study measures between chronic and episodic migraine patients. One hundred forty-seven (147) migraine outpatients from three Brazilian specialized headache hospital services completed measures of self-efficacy, locus of control, psychopathological symptoms, cognitive distortions, depression, anxiety, and headache-related disability. Headache-related cognitive distortions were positively correlated with psychopathological symptoms, depression, anxiety, pain catastrophizing, headache-related disability, headache frequency, and headache intensity. Self-efficacy beliefs correlated negatively with all psychological and clinical measures. Chance locus of control correlated positively with depression, anxiety, psychopathological symptoms, pain catastrophizing, headache-related disability, and headache intensity. Compared to episodic migraine patients, those with chronic migraine showed significantly higher levels of cognitive distortions and chance locus of control but lower levels of self-efficacy in headache management. The results brought evidence that patients' cognitive and emotional responses to their headaches are associated with headache-related disability and chronicity. Furthermore, they reinforce the need to evaluate and treat those modifiable psychological factors in daily clinical practice.